Assessing the potential for assisted gene flow using past introduction of Norway spruce in southern Sweden: Local adaptation and genetic basis of quantitative traits in trees. (22nd August 2019) - Milesi, Pascal; Berlin, Mats; Chen, Jun; Orsucci, Marion; Li, Lili; Jansson, Gunnar; Karlsson, Bo; Lascoux, Martin
Abstract: Norway spruce ( Picea abies ) is a dominant conifer species of major economic importance in northern Europe. Extensive breeding programs were established to improve phenotypic traits of economic interest. In southern Sweden, seeds used to create progeny tests were collected on about 3, 000 trees of outstanding phenotype ('plus' trees) across the region. In a companion paper, we showed that some were of local origin but many were recent introductions from the rest of the natural range. The mixed origin of the trees together with partial sequencing of the exome of >1, 500 of these trees and phenotypic data retrieved from the Swedish breeding program offered a unique opportunity to dissect the genetic basis of local adaptation of three quantitative traits ( height, diameter and bud‐burst ) and assess the potential of assisted gene flow. Through a combination of multivariate analyses and genome‐wide association studies, we showed that there was a very strong effect of geographical origin on growth ( height and diameter ) and phenology ( bud‐burst ) with trees from southern origins outperforming local provenances. Association studies revealed that growth traits were highly polygenic and bud‐burst somewhat less. Hence, our results suggest that assisted gene flow and genomic selection approaches could help to alleviate the effect of climate change on P. abies breeding programs in Sweden.